Budding Yeast Silencing Complexes and Regulation of Sir2 Activity by Protein-Protein Interactions - Tanny, Jason C. (American Society for Microbiology, 2004)
Gene silencing in the budding yeast Saccharomyces cerevisiae requires the enzymatic activity of the Sir2 protein, a highly conserved NAD-dependent deacetylase. In order to study the activity of native Sir2, we purified and characterized two budding yeast Sir2 complexes: the Sir2/Sir4 complex, which mediates silencing at mating-type loci and at telomeres, and the RENT complex, which mediates silencing at the ribosomal DNA repeats. Analyses of the protein compositions of these complexes confirmed previously described interactions. We show that the assembly of Sir2 into native silencing complexes does not alter its selectivity for acetylated substrates, nor does it allow the deacetylation of nucleosomal histones. The inability of Sir2 complexes to deacetylate nucleosomes suggests that additional factors influence Sir2 activity in vivo. In contrast, Sir2 complexes show significant enhancement in their affinities for acetylated substrates and their sensitivities to the physiological inhibitor nicotinamide relative to recombinant Sir2. Reconstitution experiments showed that, for the Sir2/Sir4 complex, these differences stem from the physical interaction of Sir2 with Sir4. Finally, we provide evidence that the different nicotinamide sensitivities of Sir2/Sir4 and RENT in vitro could contribute to locus-specific differences in how Sir2 activity is regulated in vivo.